Od adaptacji do edukacji, czyli plakaty filmowe w praktyce szkolnej - Byczek, Dominika (Załącznik Kulturoznawczy, 2023)
From Adaptation to Education: The Educational Potential of Film Posters The aim of this article is to present various possibilities for using film posters in Polish language classes during discussions of school readings. The author begins by explaining the reason for choosing this topic, which she sees primarily in the fact that, according to her own observations and research, students do not encounter the analysis of film posters in school, nor do they have a desire to respond to the demands of other researchers in the field of Polish language teaching. The text also presents a division into two types of movie posters - a photographic poster, which is a fragment of a movie frame, and an artistic poster, which is an author's creation of an artist. In the article, the author presents different possibilities for using film posters in educational practice. The proposals concern both photographic posters and artistic posters and are addressed to primary and secondary school students. The article focuses on the analysis and interpretation of colors on posters (with a focus on warm/cool colors, color palette, the meaning of colors, types of colors, their intensity, saturation, and contrast), the elements included on them (characters, their attributes, and other details), typography (with a focus not so much on the content of the text, but on its font, color, and placement), composition (placing poster elements in specific locations), discrepancies (between the content of the poster and the content of the reading), contexts (e.g., historical, socio-cultural, linguistic), emotions and moods (with a focus on students' feelings), as well as the choice itself (the author's choice and students' choice in relation to the elements included on the poster, their arrangement, colors, and all other aspects already indicated - with the possibility of creating their own film poster). In creating the article, the author repeatedly points out that the problem she analyzes constitutes a certain research gap and calls for it to be taken up by other researchers as well.